A Novel Deep Learning-based Sentiment Analysis Method Enhanced with Emojis in Microblog Social Networks. Issue 5 (4th May 2023) - Li, Xianyong; Zhang, Jiabo; Du, Yajun; Zhu, Jian; Fan, Yongquan; Chen, Xiaoliang
ABSTRACT: To exactly classify sentiments of microblog reviews with emojis in microblog social networks, this paper first proposes an emoji vectorisation method to achieve emoji vectors. Then, an emoji-text integrated bidirectional LSTM (ET-BiLSTM) model for sentiment analysis is proposed. In this model, review text-based sentence representations are extracted by a bidirectional LSTM network. Emoji-based auxiliary representations are obtained by a new attention mechanism. The two representations are further integrated into final review representation vectors. Finally, experimental results indicate that the proposed ET-BiLSTM model improves the performance of sentiment classification evaluated by macro-P, macro-R and macro-F1 scores in microblog social networks.